Penerapan Outing Class Pada Pembelajaran Sejarah Di Madrasah Aliyah Tahfizihil Qur’an - Surya Aymanda Nababan; Fikri Alkhairi; Aditya Darma (Universitas Islam Sumatera Utara, 2022)
The teaching and learning process of teachers plays an important role in the world of education and creates a smart generation in the next generation. Currently, many teachers are not innovating in the world of education and only teach with conventional methods which make students not enjoy the learning that is implemented. Many teachers only do learning in class. The teaching process in formal schools is experiencing saturation. This type of research is a descriptive qualitative research with a case study design. The data of this research is primary data which is the main data needed in this research, namely data obtained directly in the field, including data and information obtained from interviews conducted with principals, classroom teachers, and students, written data or documentation in the form of pictures/photos, learning outcomes, other literature related to the problem to be studied. The outing class that has been implemented for 3 years since the history teacher became a history teacher at Madrasah Tahfizhil Qur'an because he himself had applied it to the previous school. Outing class activities are still carried out despite changes to the curriculum in recent years. Madrasah Aliyah Tahfizhil Qur'an has changed its curriculum from the Education Unit Level Curriculum (KTSP) to the 2013 Curriculum. History learning is a process to help develop the potential and personality of students through messages. historical message to become wise and dignified citizens of the nation. History in this case is the totality of human activities in the past and is dynamic. The form of outing class learning is in the form of delivering material at the Avros plantation museum. The application of the outing class method itself has been scheduled in the Madrasah Aliyah Tahfizhil Qur'an education calendar, the process stages of which are planning, implementation, and evaluation. The benefit of outing class is that students will learn in real time, be able to interact with other people, and become students' learning motivation.